Cirrhotic cardiomyopathy - S. N. Mammayev; A. M. Karimova; T. E. Il’yasova; A. Sh. Khasayev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
The aim of review. To define cirrhotic cardiomyopathy (CCM), to reveal its pathogenic mechanisms, features of clinical manifestations, to reflect main therapeutic approaches, effect of orthotopic transplantation of liver (OTL) and transjugular portosystemic shunting (TIPS) on the course and prognosis of cardio-vascular disorders at liver cirrhosis (LC).Original positions. Disorder of signal conduction from β-adrenoreceptors, calcium channels receptors, decrease of cardiomyocyte membrane fluidity, increase of nitric oxide and carbon monoxide synthesis, elevation of endocannabinoid system activity and many other changes observed at LC, cause development of complex of structural and functional disorders in myocardium, underlying development of CCM. Results of numerous studies showed suppression of contractile response to action of various physiological and pharmacological stimuli, and disorder of diastolic function of the heart, development of electrophysiological, structural and biochemical changes at LC irrespective of its origin. Experimental and clinical data demonstrated significant improvement of cardiac activity after OTL, while TIPS acts as a kind of stress for the body, that is capable to manifest concealed disorders of cardiac activity at CCM. Low heart output at CCM in spontaneous bacterial peritonitis also increases risk of hepatorenal syndrome (HRS). Development of heart failure (HF) decompensation due to provoking factors action requires application of the standard therapeutic approaches to treatment of such patients. However there is specificity of CCM management: limited application of peripheral vasodilators, careful use of diuretics, absence of substantial effect of b1-agonists and presumably positive effect of b2-adrenoblockers on QT-interval and application of aldosterone antagonists to decrease both pre- and postload on the heart.Conclusion. In studies, that were carried out, main clinical manifestations of CCM, effect on its course and the prognosis of various pharmacological drugs, application of TIPS and OTL were demonstrated. However, further large randomized investigations devoted to diagnostics and treatment of CCM, receiving serious evidential base are necessary. Their aim should be the detailed studying of pathogenic mechanisms, development of clear standard diagnostic criteria and methods of treatment of this category of patients.